Passenger Train Discontinuance -- 30-Day Notice : hearings before the United States House Committee on Interstate and Foreign Commerce, Ninetieth Congress, second session, on Feb. 20, 1968. (U.S. Congressional Hearings., 1968)
Committee Serial No. 90-23.